Character Education in the Digital Age: Challenges and Opportunities Amidst Technological Developments - Herak, Rikardus (MSJ : Majority Science Journal, 2025)
This study aims to explore the challenges and opportunities for character education in the digital era, faced with rapid technological developments. The study used a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation studies involving teachers, students, parents, and education experts. The results indicate that the main challenges in character education in the digital era include social media addiction, decreased direct social interaction, and low digital literacy among teachers and parents. However, opportunities for character strengthening remain open through the use of digital platforms such as educational videos, interactive applications, and social media to campaign for positive values. Strengthening strategies are needed, such as increasing digital literacy, integrating character education into technology-based learning, and multi-stakeholder collaboration between schools, parents, and the community.